(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to address student passivity in English language learning at SMA Nurul Jadid through the implementation of classroom speaking activities. Student passivity, manifested through sleeping behavior during lessons, presents a serious challenge that impedes language acquisition. The research employed Classroom Action Research (CAR) methodology following Kemmis and McTaggart’s model, consisting of four stages: planning, acting, observing, and reflecting, conducted over two cycles with each cycle comprising two sessions. Data collection techniques included observation checklists, field notes, video recordings, and semi-structured interviews with students and teachers. The findings demonstrate significant success in reducing student passivity. In Cycle 1, sleeping behavior decreased from 37.5% to 9.4%, while active participation increased from 25% to 68.8%. Cycle 2 showed dramatic improvements with complete elimination of sleeping behavior (0%), active participation rising to 90.6%, and average speaking time increasing by 1,092% compared to baseline conditions. A total of 90.6% of students expressed desire for more speaking activities in future lessons. This research concludes that systematically designed, varied, and appropriately scaffolded speaking activities can effectively transform passive learning behaviors into active participation patterns in Indonesian high school English classrooms.